Quality Education and Skills of Indonesian Labor, Towards Equality Wages in Foreign Countries - Febriani, Febriani (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2013)
This study examines the influence of the quality of education and skills of prospective Indonesia Labor from West Sumatra on income. Wage income is expected equivalent to the level of wage labor which comes from other countries. Therefore, in order to obtain equal wage, prospective Indonesian labors sent abroad should be a good level of education, skill trained so that labor productivity increased. The method used in this study is Test Crosstab, and, Chi Square test to see the effect between the two variables used. It is shown that Indonesian labors do not able to compete in terms of quality of education and skills, compared to foreign labors, so that the income received by the Indonesian labor is lower. In addition, professional job that has been chosen by the Indonesian labor is the operator, profession which does not necessarily require a high level of educational and skills qualifications.